2005
DOI: 10.2175/106143005x73974
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Aeromonas spp in Water from Drinking‐Water‐ and Wastewater‐Treatment Plants in México City

Abstract: The frequency of Aeromonas spp in three wastewater‐treatment plants (WWTPs) and two drinking‐water plants (DWPs) in México City was determined. Samples were taken throughout a year by the Moore's swab technique. A total of 144 samples were obtained from WWTPs and 96 from DWPs of both incoming and outflowing water. Aeromonas spp was isolated in 31% of the samples, from both kinds of sources. The technique used for the isolation of the pathogen was suitable for samples with high associate microbiota content and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Ribeiro et al (2010) Aeromonas species are the most common organisms reported in infections of burns exposed to contaminated water. However, Lamy et al Polluted aquatic environments can be considered a source of contamination for recreational waters and water used in the irrigation process (Villari et al 2000;Davies et al 2001;Uyttendaele et al 2004;Vally et al 2004;Villarruel-Ló pez et al 2005;Daskalov 2006;Dwivedi et al 2008). Besides the determination of indicator bacteria, it is important to understand the distribution of potentially doi: 10.2166/wh.2010.140 pathogenic bacteria in a given ecosystem that could affect natural water used for human contact or consumption (Nagvenkar & Ramaiah 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (2010) Aeromonas species are the most common organisms reported in infections of burns exposed to contaminated water. However, Lamy et al Polluted aquatic environments can be considered a source of contamination for recreational waters and water used in the irrigation process (Villari et al 2000;Davies et al 2001;Uyttendaele et al 2004;Vally et al 2004;Villarruel-Ló pez et al 2005;Daskalov 2006;Dwivedi et al 2008). Besides the determination of indicator bacteria, it is important to understand the distribution of potentially doi: 10.2166/wh.2010.140 pathogenic bacteria in a given ecosystem that could affect natural water used for human contact or consumption (Nagvenkar & Ramaiah 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some authors consider that these organisms should be a sanitary quality indicator (7,19,21,24). Moreover, Aeromonas hydrophila is listed in the first and second Contaminant Candidate List (CCL1 and CCL2) by the US Environmental Protection Agency -USEPA (26), linking these organisms to public health adverse outcomes.…”
Section: Study Areamentioning
confidence: 99%
“…These organisms are largely distributed in several water sources such as rivers, lakes, wells, sewage, wastewaters and drinking water supplies (19,24).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations